Primary Breast Mucosa-Associated Lymphoid Tissue (MALT) Lymphoma Transformation to Diffuse Large B-cell Lymphoma: A Case Report - Arslan, Şerife Hülya (Galenos Publishing, 2012)
Primary non-Hodgkin’s lymphoma (NHL) of the breast constitutes 0.04%-0.53% of all malignancies and 2.2% of extra nodal lymphomas. In total, 7%-8% of all B-cell lymphomas are the mucosa-associated lymphoid tissue (MALT) type, of which up to 50% of primary gastric MALT lymphoma. Herein we present a patient with breast MALT lymphoma that transformed to diffuse large B-cell lymphoma (DLBCL). A 69-year-old female presented with a mass on her left breast. Physical examination showed a 3×3-cm mass located 1 cm from the areola on the upper lateral quadrant of the breast at the 1 o’clock position, which was fixed and firm. Excisional biopsy was performed and pathologic examination of the specimen showed MALT lymphoma transformation to DLBCL. The patient was staged as II-EA. The rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP) protocol was scheduled as treatment. Following 6 courses of R-CHOP, 2 additional courses of rituximab were administered. Positron emission tomography (PET)-CT was done at the end of the treatment. PET showed that the patient was in complete remission. At the time this report was written, the patient was being followed-up at the outpatient clinic on a regular basis. Lymphoma of the breast is a rarity among malignant tumors of the breast. The most common type of lymphoma is DLBCL. Breast MALT lymphoma is extremely rare. Primary MALT lymphoma of the breast can transform from low grade to high grade and recurrence is possible; therefore, such patients should be monitored carefully for transformation.